Sensory Marketing: The Effect of Tactile Cue on Product Packaging towards Perceived Novelty and Perceived Likeability - Rifqiya, Afwan; Nasution, Reza Ashari (Journal of Business and Management, 2016)
Abstract. According to the research conducted by Boston Consulting Group (BCG) in 2015, Indonesian consumer usually will not try for new brands unless they have had a negative experience with a product used in the past. On the other hand, they could try new a product if they hear or know something significant about a new product or the product feature. Therefore marketers need to find new and innovative strategies to interact with the customer. As the sensory marketing emerges as the new strategy in recent pass years, there is one sense that has started to break a new ground and seize the attention of researchers and marketers all around the world, which is the sense of touch or tactition. In particular, the research examined the utilization of tactile cue on product packaging as the new strategy towards perceived novelty and perceived likeability. Furthermore, nowadays less research is explored regarding the potential impact of the tactile cue on product packaging. The study constructed in experimental research design and analyzed by using Paired t-test and Wilconox signed-rank Test. The finding shows customer feel the novelty and more prefer towards the packaging that utilized tactile cue. Consequently, it could increase the opportunity for the product to be chosen by customer. However, further research has to be done regarding the relationship between tactile cue and customer’s purchase decision to obtain more impactful result in utilizing tactile cue on the product packaging.Keywords: Sensory marketing, Tactile cue, Product packaging.